SOIL SYSTEM AND PEDOGENIC PROCESSES: SELF-ORGANIZATION, TIME SCALES, AND ENVIRONMENTAL SIGNIFICANCE - Targulian V.O.; Krasilnikov P.V. (My University, 2007)
The essence of pedogenesis, as a synergetic process, consists in generation, selection, accumulation and differentiation of the solids produced in the course of bio-abiotic processes functioning within a soil body. Soil formation in the broad sense is the result of synergetic processes of self-organization of an in situ soil system during its functioning in time and space. Soil formation, sensu stricto, is the transformation of the solid-phase lithomatrix (parent material) of the soil system into the pedomatrix (soil body, soil mantle). Pedogenesis is perceived as an integration of specific pedogenic processes (SPP); each of them characterized by a definite set of solid-phase pedogenic features. Each soil body is formed by a combination of some SPP. The whole set of SPP may be grouped in accordance with their essence, characteristic times (rates) and reversibility-irreversibility. In terms of characteristic times (rates) they may be arranged in three main groups: rapid (101-2 years), medium-rate (103-4 years), and slow (105-6 years). Soil system functioning and soil formation are intimately linked but fundamentally different processes: the former is infinite in time, if not interrupted by external factors; the latter, as any self-organization process, is finite in time and tends to reach a steady state. The theoretical grouping of the pedogenic processes according to their essence and self-termination or quasi-equilibrium is proposed. All the diagnostic soil horizons (as defined in WRB) are perceived as more or less stable and "mature" degrees of soil self-development. They may be separated into favorable and unfavorable with respect to their suitability for biota. Favorable conditions are generally common in 12 out of 39 diagnostic horizons and properties (32%). They are mainly influenced by biotic fluxes and cycles, which are comparable to, or exceed, abiotic fluxes and cycles in their strength and capacity. In this case, biota transforms and improves the environment rather than adapts to it. Unfavorable conditions are more common in 27 out of 39 diagnostic horizons and properties (68%). They are influenced by the mutual action both of biotic and abiotic fluxes and cycles. In this case, biota adapts to the environment rather than improves it. © 2007 Elsevier B.V. All rights reserved.
Keywords: DIAGNOSTIC HORIZONS; PEDOGENESIS RATES; SOIL ECOLOGICAL FUNCTIONS; WRB